Onyùmə́nyùmà, le règne olfactif chez les Fang-Ntumu du Gabon - Régis Ollomo Ella (Revue d'ethnoécologie)
When you talk about ènyùm ‘’odour’’ to a Fang-Ntumu speaker, his first reaction is disgust. For this people, ènyùm ‘’odour’’ seems to deal with ènyùm àbé ‘’bad odour’’.This paper is about ònyùmə́nyùmà, that Fang-Ntumu’s olfactory surroundings. It will answer to three principal questions: What’s smell? What does it smell? How does it smell? In this paper we shall identify and classify odorous sources, and producted odours. In addition, we’ll study own Fang-Ntumu odours classification, and determine the deeper principle which explain their olfactory judgment.